Diagnostic value of cerebrospinal fluid lactate as a biomarker of bacterial meningitis (European Journal of Health Research, 2021)
Bacterial meningitis is a serious pathology that requires an accurate and early diagnosis. Increased leukocytes, with a predominance of polymorphonuclear cells, increased proteins, and hypoglycorrhachia are indicative of a bacterial etiology, although they do not always correlate with a definitive diagnosis. The aim of this study was to evaluate the usefulness of cerebrospinal fluid lactate as a biomarker of bacterial meningitis.This is an observational and prospective study in which 706 cerebrospinal fluids from patients treated at the Virgen de Valme University Hospital (Seville, Spain) for 20 months were analyzed. Of the fluid analyzed, in 21 cases bacterial meningitis was diagnosed, in 31 cases bacterial meningitis was compatible, and in 654 cases bacterial meningitis was ruled out. The optimal cut-off point for lactate in cerebrospinal fluid was 3.0 mmol/L, with a sensitivity of 68%, a specificity of 98%, a positive predictive value of 79%, and a negative predictive value of 97%.Lactate concentration, protein concentration, and the number of leukocytes in cerebrospinal fluid were significantly higher in patients with confirmed bacterial meningitis. The high negative predictive value of lactate is especially useful to rule out bacterial meningitis in sick patients. Lactate is the biomarker with the best diagnostic performance of all those analyzed, so we recommend its inclusion in the cerebrospinal fluid biochemical profile.
Keywords: bacterial meningitis; cerebrospinal fluid; lactate